Early Rearing Conditions Affect Monoamine Metabolite Levels During Baseline and Periods of Social Separation Stress: A Non-human Primate Model (Macaca mulatta) - Wood, Elizabeth K.; Gabrielle, Natalia; Hunter, Jacob; Skowbo, Andrea N.; Schwandt, Melanie L.; Lindell, Stephen G.; Barr, Christina S.; Suomi, Stephen J.; Higley, J. Dee (Frontiers in Human Neuroscience, 2021)
A variety of studies show that parental absence early in life leads to deleterious effects on the developing CNS. This is thought to be largely because evolutionary-dependent stimuli are necessary for the appropriate postnatal development of the young brain, an effect sometimes termed the “experience-expectant brain”, with parents providing the necessary input for normative synaptic connections to develop and appropriate neuronal survival to occur. Principal among CNS systems affected by parental input are the monoamine systems. In the present study, N=434 rhesus monkeys (233 males, 201 females) were reared in one of two conditions: as mother-reared controls (MR; n=269) or without adults with 24-hour access to same-aged peers (PR; n=165). When subjects were six-months-old, they underwent a separation paradigm involving 4, sequential, four-day social separations from their mothers (MR) or peers (PR), with each separation followed by three-day reunions with their mothers or their peers. Prior to the separation paradigm, baseline cisternal CSF samples were obtained, as well as at the end of each the four social separations, and after final separation, during a recovery period. CSF was assayed for concentrations of monoamine metabolites and a blood sample was genotyped for the serotonin transporter (5-HTT) genotype. Replicating earlier landmark findings, PR subjects with the s allele exhibited lower baseline concentrations of the serotonin metabolite 5-hydroxyindoleacetic acid (5-HIAA), when compared to PR subjects homozygous for the L allele. MR subjects were undifferentiated by genotype. PR subjects exhibited lower CSF 5-HIAA concentrations during baseline, but higher CSF 5-HIAA during social separations, when compared to MR subjects. There were rearing effects for the dopamine metabolite homovanillic acid (HVA) and for the norepinephrine metabolite 3-methoxy-4-hydroxyphenylglycol (MHPG), with PR subjects showing higher HVA and lower MHPG when compared to MR subjects. These findings indicate that there are long-term deficits in the response of monoamines following maternal absence. The results of this study confirm and extend earlier findings that early life parental absence has deleterious consequences for the development of the monoamine systems, and that these consequences are modulated by the 5-HTT genotype.